Guyton and Hall Textbook of Medical Physiology - Hall, John E.; Hall, Michael E. (India: Elsevier, 2021)
"This is a comprehensive textbook of medical physiology"--
Includes bibliographical references and index.
Keywords: Human physiology; Physiology, Pathological